Silver-coated PMMA nanoparticles-on-a-mirror substrates as high-performance SERS sensors for detecting infinitesimal molecules - Pei Zeng; Yuting Zhou; Hao Chen; Yifei Fu; Meiyan Pan; Guanying Chen; Xing Yang; Qing Liu; Mengjie Zheng (Scientific Reports)
Abstract Surface-enhanced Raman scattering (SERS) technology has attracted more and more attention due to its high sensitivity, low water interference, and quick measurement. Constructing high-performance SERS substrates with high sensitivity, uniformity and reproducibility is of great importance to put the SERS technology into practical application. In this paper, we report a simple fabrication process to construct dense silver-coated PMMA nanoparticles-on-a-mirror SRES substrates. The electric field enhancement at the ultra-small metallic nanogap is further amplified by the silver mirror, which can achieve higher SERS intensity. The thickness of the PMMA layer was optimized so that the absorption peak can match the excitation wavelength, thus obtaining maximum SERS intensity. The optimized substrate possessed excellent SERS behavior for crystal violet (CV) molecules under 532 nm laser excitation, with a low detection limit of 10− 13 M. Moreover, SERS analysis was quantitatively achieved in the broad linear concentrations. The fabricated substrate demonstrated excellent uniformity and reproducibility with a relative standard deviation (RSD) of 7.75% in peak intensities. The substrate also showed long-term stability, and it can be stored for 37 days with an acceptable SERS peak intensities. This proposed method will open up new possibilities to fabricate high-performance SERS sensors, which can be widely used for the practical application of chemical and biochemical sensing.